FTMSK Resources Scheduling System (FRSS) / Maria Kamaruddin @ Yin - Kamaruddin @ Yin, Maria (Faculty of Computer and Mathematical Sciences, 2005)
Resource scheduling is the crucial task to ensure that rooms, lesson and lab equipment and other resources are available to the right people at the right time. The algorithms used for academic scheduling are very sophisticated to the work of scheduling and maintaining group. This project is about the FTMSK Resources Scheduling System (FRSS) where it is a system allowed users to make a booking easily by selecting required information. It provides a fimctionahty to enable users to make a booking without a problem such as redundant book. An administrator can maintain the resources so job can be even easier.